The Shaping of 'Abbasid Rule - Lassner, Jacob (Princeton Studies on the Near East, 2017)
In order to understand the transition between the revolutionary movement that propelled the Abbasids to power and the imperial government that later took root, Jacob Lassner studies those elements that served to shape the political attitudes and institutions of the emerging regime during its formative years.Originally published in 1980.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905